Propuesta de mejora en la gestión de venta de arándano premium en el mercado chino - Villavisencio Rios, Marco Eduardo (2024)
The following paper shows an improvement proposal on a sales management strategy for premium blueberries in the Chinese market for the 2020 – 2021 season. This proposal was evaluated and implemented at Blueberries Peru´s facilities, located in Chao Valley, district of Virú in La Libertad region and the Chinese market. Bearing in mind the scopes and limitations in the country of origin and the chosen market, we defined the characteristics of a premium berry, chose the ideal variety from the right area through an evaluation of weather conditions and historical data. Additionally, Lean Manufacturing tools were implemented in the packing house to avoid possible deviations in the final product. Further on, through a strategy of differentiation with a premium product we obtained a better season average return for the mentioned period. In a market with year-by-year increasing volumes and declining prices trends, the development of better sales management strategies is essential to guarantee the profitability of the business in the medium or long term.